Пізньопалеолітичний комплекс Великих Дивлин на півночі Житомирщини - Шидловський, П.С.; Хоптинець, І.М. (Кам’яна доба України, 2010)
Стаття вводить у науковий обіг нові матеріали з двох пізньопалеолітичних пам’яток Великий Дивлин А та Е, розташованих біля однойменного села на півночі Житомирщини. Порівняльний аналіз типологічних і технологічних особливостей колекцій та залучення аналогій з інших територій свідчить про належність пам’яток до різних культурно-хронологічних епізодів у межах кінця палеолітичної епохи. This paper presents new palaeolithic finds that were discovered during investigation a new Upper Palaeolithic complex of sites “Velykyj Dyvlyn” (North of Zhytomyr region).The article considers the location of the sites, topography and technology of flint working. By the analysis of flint materials from two localities A and E we can get the conclusions about different traditions of flint working. One tradition (locality A) connected with “ovruchien” variant of epigravettian circle, presented by the sites of North Zhytomyr region
(Dovgynychi, Zbranky, Sholomky). Another tradition (locality E) has more analogies among the Final Palaeolithic complexes of Europe. Authors interpret these localities as a rests of temporary camps of different hunters collectives. Further researches will give us a new data about cultural and chronological variability of Upper Palaeolithic culture of Northern Ukraine.